Integrated electron microscopy: super-duper resolution - Krijnse-Locker, Jacomine; Schmid, Sandra Louise (PLoS biology, 2013)
New developments in electron microscopy used in combination reveal the elegant architecture of cellular structures at very high resolution.
Gesehen am 19.05.2021